# Geometric progressionProve that the series that have the sum of the n terms Sum=4^n -1, is a geometric progression.

### 2 Answers | Add Yours

The sum of n terms of the series is given by 4^(n -1)

The sum of n + 1 terms is 4^(n + 1 - 1) = 4^n

The sum of n - 1 terms is 4^(n - 1 - 1) = 4^n/16

We see that the (n - 1)th term is 4^n/16, the nth term is 4^n/4 and the (n + 1)th term is 4^n.

4^n/(4^n/4) = (4^n/4)/(4^n/16) = 4

Each of the terms has a common ratio of 4.

**This proves that the series is a geometrical progression**

If we want to prove that the given series is a geometrical progression, we'll have to substantiate that having 3 consecutive terms of the progression, the middle one is the geometric mean of it's neighbors.

We'll determine the general term bn, and after finding it, we'll utter any other term of the progression.

From enunciation:

Sn=b1+b2+b3+...+bn

(4^n)-1=b1+b2+b3+...+bn

bn=(4^n)-1-(b1+b2+b3+...+b(n-1))

But (b1+b2+b3+...+b(n-1))=S(n-1)=[4^(n-1)]-1

bn=(4^n)-1-4^(n-1)+1

bn=4^n(1-1/4)=4^n*3/4=3*4^(n-1)

We'll express 3 consecutive terms, b1,b2,b3.

b1=3*4^0

b2=3*4^(2-1)=3*4

b3=3*4^(3-1)=3*4^2

Following the rule enunciated above, we'll verify if

b2=sqrt (b1*b3)

3*4= sqrt(3*1*3*16)

3*4=3*4

Sn is a geometrical progression!